Performance Measures of Competitive and Noncompetitive Companies in Malaysia - Ong, Tze San (2001)
This study aims to document the current performance measures used by organizations in Malaysia. The purposes of having performance measures and limitations encountered in implementing their performance measurement systems were also examined. Most of the very competitive organizations achieved all their organisation's goals or objectives compared to the non-competitive organisations. The majority of the organizations irrespective of their competitiveness, were concerned the performance measurement systems in the organizations Cash flow, collection period, payment period, gearing ratio and profitability ratios were frequently used accounting performance measures. Capital utilization, labour productivity, inventory level, schedule adherence and supplier product quality were the more frequently employed performance measures in the production functions. As for the marketing functional area, product quality is the most frequently used measure, followed by the price of the product and number of customer complaints. As the capital investment is concerned, payback was the most widely used performance measure and followed by net present value. Majority of the respondents were satisfied with their existing performance measurement systems. Overall, there are no significant differences in the performance measures used between competitive and non-competitive companies.